PERAN STATSMAN PADA MOBILE LEGEND PROFESIONAL LEAGUE TOURNAMENT 2018 oleh RevivaLTV - Aditya Achmad Kurnia; Rimsky K. Judiseno (Bisnis Event, 2020)
Mobile Legend Professional League (MPL) is the largest and most prestigious gadget competition game in Southeast Asia that will feature a game called Mobile Legend: Bang Bang. Mobile Legend Professional League has become one of the esport tournaments that is highly anticipated by all fans of mobile legend games and also fans of tournament esport, because Mobile Legend Professional League will be one of the biggest esport gadget competition events in Southeast Asia. Statsman has an important role in the esport tournament, which is processing data from a game to create interesting visual graphics, and making the event more accessible to the audience. Statsman became a crucial division in organizing esports tournaments. One of the method done by statsman in processing match data and presented in interesting way is using the Echo application system which is a system application that is used to support ongoing players in an esport, and dynamically displays data into interesting graphics to give to the audience. This study uses observational data collection methods with qualitative descriptive analysis methods. The results of this study were to study the role of statsman in the activities of Mobile Legend Professional League season 2.